1999
DOI: 10.1021/la981720a
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of a Ligand-Preserved Giant Palladium Cluster on a Metal Oxide Surface and Its Nobel Heterogeneous Catalysis for Oxidation of Allylic Alcohols in the Presence of Molecular Oxygen

Abstract: A 1,10-phenanthroline (phen) ligand-preserved five-shell giant palladium cluster, Pd5(phen), could be uniformly immobilized on a neutral TiO2 surface while keeping its original cluster size of ca. 30 Å and local ordering around Pd atoms. The Pd5(phen)/TiO2 acted as an efficient and reusable heterogeneous catalyst for the oxidations of primary allylic alcohols into the corresponding α,β-unsaturated aldehydes in the presence of molecular oxygen as well as the corresponding homogeneous Pd5(phen) cluster. Roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Among various metal/metal oxide composite nanostructures, supported Pd nanocatalysts have been found to play an important role for a number of reactions, including hydrogenation reaction, the carbon-carbon cross-coupling reaction, the oxidation of primary alcohols, the direct generation of H 2 O 2 from H 2 and O 2 , and so on [27][28][29][30]. Recently, Lee et al [31] reported the preparation of Pd/ SnO 2 composite nanorods by using NaBH 4 as reducing agent via a solution process, but the size of the Pd nanoparticles is large, limited their applications in the catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among various metal/metal oxide composite nanostructures, supported Pd nanocatalysts have been found to play an important role for a number of reactions, including hydrogenation reaction, the carbon-carbon cross-coupling reaction, the oxidation of primary alcohols, the direct generation of H 2 O 2 from H 2 and O 2 , and so on [27][28][29][30]. Recently, Lee et al [31] reported the preparation of Pd/ SnO 2 composite nanorods by using NaBH 4 as reducing agent via a solution process, but the size of the Pd nanoparticles is large, limited their applications in the catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…3 nm in size) immobilized on TiO 2 catalyzed the oxidation of primary alcohols by oxygen in acetic acid. [5] A bipyridylamide-bound ionic Pd species located inside the mesoporous channels of SBA-15 could catalyze the aerobic oxidation of alcohols in the presence of K 2 CO 3 in toluene, [6] but it was also pointed out that the derived Pd nanoparticles may also account for the actual activity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising properties is porosity in the support material, to act as a molecular transport pathway to the active catalyst surface and to improve the total reaction rate and product selectivity. In order to prepare heterogeneous catalysts with metallic nanoparticles, including Pd, or to prevent nanoparticles from coalescing, various types of inorganic shells, such as silica [7][8][9], carbon and metal oxides around the nanoparticles, may be used [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%